Improvement of blood glucose control and reduction of hypoglycemia, body weight, and C-reactive protein in type 1 diabetic patients treated with intensive insulin therapy with insulin analogs - Radenković, Saša; Velojić Golubović, Milena; Dimić, Dragan; Radojković, Danijela; Ćirić, Vojislav; Pešić, Milica (Vojnosanitetski pregled, 2024)
Background/Aim. Good metabolic control can delay the onset and progression of chronic complications of diabetes mellitus (DM). Intensified insulin therapy (IIT) is the cornerstone of good metabolic control in the treatment of type 1 DM (T1DM) while avoiding hypoglycemia and body weight (BW) gain in those patients. The aim of the study was to assess the effects of IIT with insulin analogs (aspart and glargine) in T1DM patients. Methods. This prospective clinical study included 49 patients with at least one year of T1DM duration, who were on IIT with human insulin at that moment. They commenced therapy with insulin aspart for three months, followed by insulin glargine for another three months. An analysis of blood glucose (BG) control (glycated hemoglobin – HbA1c, mean BG, fasting BG, postprandial BG, and glycemic variability) and analysis of BW, hypoglycemia, and C-reactive protein (CRP) levels were performed. Results. The HbA1c level decreased slightly (non-significantly) after three months of insulin aspart therapy (from 9.28% to 8.83%) and decreased significantly after the aspart/glargine combination (to 8.08%; p < 0.001). After the first three months with aspart therapy, a significant reduction in postprandial BG was noted after all three main meals. The mean postprandial rise of BG was significantly reduced. The variability of daily BG was significantly reduced (standard deviation of BG fell from 2.28 mmol/L to 1.90 mmol/L; p < 0.05). The mean BG value in the profiles decreased (from 9.11 mmol/L to 8.31 mmol/L; p < 0.05). All BG values in the profiles after six months were statistically significantly lower compared to the initial values, as well as the mean BG (6.88 mmol/L; p < 0.001) and the variability of daily BG (1.49 mmol/L; p < 0.01). Our results showed a significant reduction in the number of hypoglycemias after three months, especially after the introduction of insulin glargine therapy (significant reduction in the number of symptomatic, asymptomatic, and nocturnal hypoglycemias). The results showed a discrete but significant reduction in BW and a significant reduction in CRP levels (from 3.43 mg/L to 2.25 mg/L; p < 0.001). Conclusion. Treatment of patients with T1DM with insulin analogs (insulin aspart and insulin glargine) in IIT leads to improved BG control with a reduction in the number of hypoglycemia, BW, and CRP levels.